Síntese, caracterização e estudo das propriedades magnéticas do óxido de zinco dopado com cério (Zn1 -xCexO) - Lourenço, Marcelo Mendes (2013)
Nanoparticles of zinc oxide doped cerium (Zn1 -xCexO) with 0.0 ≤ x ≤ 0,48% were synthesized by forced hydrolysis reaction. Structural analysis of samples was performed by X-Ray Diffraction (XRD) powder method. The chemical analysis was performed by EDS, Photo Electron Spectroscopy Excited X-ray (XPS) and Spectroscopy Infrared Fourier Transform (FTIR). Thermal analysis was obtained by Thermogravimetry (TG) analysis and magnetic analysis was performed by Magnetometry Vibrating Sample (VSM). The chemistry analysis by EDS show the samples presented amounts of the Ce with 0,0 ≤ x ≤ 0,48% . The samples presented phases corresponding the hexagonal wurtzite system compact and absence of secondary phases in the sample without heat treatment and with low amounts of dopant (2.5%). The average particle diameter was 29 nm calculated by the Scherrer equation. Chemical analysis by XPS showed peaks of greater intensity associated with the elements Zn, O and Ce being confirmed tetravalent oxidation state to the dopant (Ce4+). FTIR analysis revealed the presence of connections Zn-O type, presence of organic residues and displacement bands possibly related to the presence of dopant. Thermogravimetric analysis revealed the presence of organic residues present in the samples and a mass gain of ~ 0.2% probably associated with the formation of secondary phase of CeO2. The magnetic analyzes revealed that the samples show ferromagnetism at room temperature with coercive field (Hc) of between 60 and 90 Oe and remnant magnetization (Mr) on the order of 10-4 emu/g. The evaluation of the magnetic sample to 0,22% (Zn0,9978Ce0,0022O), heat treated, showed a reduction in the magnetic behavior of this sample with increasing heat treatment temperature.